An Assessment of the Professional Development Needs of English Teachers in Carrascal National High School Regarding 21st-Century Skills. - Arreza, Jenie; Lagura, Keetlyn (JPAIR Institutional Research, 2026)
This paper presents a conceptual framework and a proposed quantitative study to investigate the professional development needs of English teachers, with a specific focus on the acquisition of 21st-century skills. The literature review establishes the causal link between a teacher’s years of experience and their evolving professional needs, arguing that a one-size-fits-all approach to training is ineffective. It synthesizes research on the distinct needs of novice, mid-career, and experienced teachers, highlighting gaps in practical pedagogy, technology integration, and assessment literacy. The proposed methodology outlines a survey-based approach to measure self-assessed knowledge and perceived needs, with a plan for statistical analysis to determine correlations and significant differences across experience levels. The findings of such a study would provide a nuanced understanding crucial for designing targeted and impactful professional development programs.